A Nanopore Based Chromosome-Level Assembly Representing Atlantic Cod from the Celtic Sea. Issue 9 (1st September 2020) - Kirubakaran, Tina Graceline; Andersen, Øivind; Moser, Michel; Árnyasi, Mariann; McGinnity, Philip; Lien, Sigbjørn; Kent, Matthew
Abstract: Currently available genome assemblies for Atlantic cod ( Gadus morhua ) have been constructed from fish belonging to the Northeast Arctic Cod (NEAC) population; a migratory population feeding in the Barents Sea. These assemblies have been crucial for the development of genetic markers which have been used to study population differentiation and adaptive evolution in Atlantic cod, pinpointing four discrete islands of genomic divergence located on linkage groups 1, 2, 7 and 12. In this paper, we present a high-quality reference genome from a male Atlantic cod representing a southern population inhabiting the Celtic sea. The genome assembly (gadMor_Celtic) was produced from long-read nanopore data and has a combined contig length of 686 Mb with an N50 of 10 Mb. Integrating contigs with genetic linkage mapping information enabled us to construct 23 chromosome sequences which mapped with high confidence to the latest NEAC population assembly (gadMor3) and allowed us to characterize, to an extent not previously reported large chromosomal inversions on linkage groups 1, 2, 7 and 12. In most cases, inversion breakpoints could be located within single nanopore contigs. Our results suggest the presence of inversions in Celtic cod on linkage groups 6, 11 and 21, although these remain to be confirmed. Further, we identified a specific repetitive element that is relatively enriched at predicted centromeric regions. Our gadMor_Celtic assembly provides a resource representing a 'southern' cod population which is complementary to the existing 'northern' population based genome assemblies and represents the first step toward developing pan-genomic resources for Atlantic cod.